Epigallocatechin Gallate and Sulforaphane Combination Treatment Induce Apoptosis in Paclitaxel-Resistant Ovarian Cancer Cells through hTERT and Bcl-2 Down-regulation - Chen, Huaping (2013)
The cellular development of resistance to chemotherapy contributes to the high mortality noted in patients affected by ovarian cancer. Novel compounds that specifically target cellular drug resistance in ovarian cancer are therefore highly desired. Previous epidemiological studies indicate that consumption of green tea and cruciferous vegetables is inversely associated with occurrence of ovarian cancer. Therefore revealing the effects and mechanisms of major components of green tea (epigallocatechin gallate, EGCG) and cruciferous vegetables (sulforaphane, SFN) on ovarian cancer cells will provide necessary knowledge for developing potential novel treatments for the disease. In this study, EGCG or SFN was used to treat both paclitaxel-sensitive (SKOV3-ip1) and -resistant (SKOV3TR-ip2) ovarian cancer cell lines alone or in combination. We found that SFN inhibits cell viability of both ovarian cancer cell lines time- and dose-dependently and that EGCG potentiates the inhibiting effect of SFN on ovarian cancer cells. Cell cycle analysis indicates SFN can arrest ovarian cancer cells in G2/M phase, while EGCG and SFN co-treatment can arrest cells in both G2/M and S phase. Combined EGCG and SFN treatment increases apoptosis significantly in paclitaxel-resistant SKOV3TR-ip2 cells after 6 days of treatment, while reducing the expression of hTERT, the main regulatory subunit of telomerase. Western blotting also indicates that SFN can down-regulate Bcl-2 (a gene involved in anti-apoptosis) protein levels in both cell types. Cleaved poly(ADP-ribose) polymerase (PARP) becomes up-regulated by 6 days of treatment with SFN and this is more pronounced for combination treatment indicating induction of apoptosis. Furthermore, phosphorylated H2AX is up-regulated after 6 days of treatment with SFN alone, and EGCG can potentiate this effect, suggesting that DNA damage is a potential cellular mechanism contributing to the inhibiting effect of EGCG and SFN combination treatment. Taken together, these results indicate that EGCG and SFN combination treatment can induce apoptosis by down-regulating of hTERT and Bcl-2 and promote DNA damage response specifically in paclitaxel-resistant ovarian cancer cell lines and suggest the use of these compounds for overcoming paclitaxel resistance in ovarian cancer treatment.